1901 Ariz. Sess. Laws 1248 - (:unkn) unknown (My University, 1901)
Prohibited the selling, giving, renting, bartering, or furnishing of any rifles, carbines, pistols, revolvers, ammunition, or cartridges to Indians. Violators guilty of a misdemeanor, punishable by imprisonment not less than one or more than six months, or by fine not less than fifty nor more than three hundred dollars, or both.
Keywords: TRANSFER - DANGEROUS PERSONS